PENGARUH KESADARAN WAJIB PAJAK, PEMAHAMAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI PASAR TOHAGA CIBINONG - Muhammad Rizki; Khoirina Farina (Universitas Trilogi, 2022)
This study aims to analyze taxpayer awareness, understanding of taxation, and tax sanctions on MSME taxpayer compliance. The sample used in this study is MSME taxpayers in the Cibinong Tohaga Market as many as 100 respondents. The sampling technique used in this research is purposive sampling. The type of data used is primary data. This type of research is quantitative research with data collection techniques, namely the method of distributing questionnaires through google form using a Likert scale. The data analysis technique in this study was carried out using the SmartPLS version 3.2.9 software program method. The results of this study indicate that tax sanctions have a positive and significant effect on MSME taxpayer compliance. Meanwhile, taxpayer awareness and understanding of taxation have no effect on MSME taxpayer compliance. Keywords: Taxpayer Compliance; Taxpayer Awareness; Tax Understanding; Tax Sanctions